On the Pterostichus subgenus Wraseiellus from China: descriptions of five new species and supplementary notes on taxonomy (Coleoptera: Carabidae) - Chen, Jia-Heng; Yin, Wen-Qi; Shi, Hong-Liang (Zootaxa, 2024)
A total of five new species of the subgenus Wraseiellus Shi & Sciaky, 2013 are described: P. (Wraseiellus) hemichlorus sp. nov. (Xizang, Gyirong County, alt. 2934m), P. (Wraseiellus) idiopterus sp. nov. (Yunnan, Weixi County, alt. 2771m), P. (Wraseiellus) pseudandrewesi sp. nov. (Sichuan, Butuo County, alt. 3218m), P. (Wraseiellus) leishanensis sp. nov. (Guizhou, Leigongshan, alt. 2110m) and P. (Wraseiellus) strumatus sp. nov. (Sichuan, Emeishan, alt. 1900m). Supplementary subgeneric diagnosis and an updated key to the subgenus Wraseiellus are provided, based on all thirteen recognized species and one subspecies.